High seroprevalence of SARS-CoV-2 but low infection fatality ratio eight months after introduction in Nairobi, Kenya. (November 2021) - Ngere, Isaac; Dawa, Jeanette; Hunsperger, Elizabeth; Otieno, Nancy; Masika, Moses; Amoth, Patrick; Makayotto, Lyndah; Nasimiyu, Carolyne; Gunn, Bronwyn M.; Nyawanda, Bryan; Oluga, Ouma; Ngunu, Carolyne; et al.
Highlights: A population-based, cross-sectional serosurvey of SARS-CoV-2 in Nairobi, Kenya Over one-third of Nairobi residents had been exposed to SARS-CoV-2 Evidence of extensive transmission was similar to or higher than Europe or the USA Persons aged 20-59 years had at least two-fold higher seropositivity than those aged 0-9 years The infection fatality ratio was >10-fold lower than that reported in Europe or the USA ABSTRACT: Background: The lower than expected COVID-19 morbidity and mortality in Africa has been attributed to multiple factors, including weak surveillance. This study estimated the burden of SARS-CoV-2 infections eight months into the epidemic in Nairobi, Kenya. Methods: A population-based, cross-sectional survey was conducted using multi-stage random sampling to select households within Nairobi in November 2020. Sera from consenting household members were tested for antibodies to SARS-CoV-2. Seroprevalence was estimated after adjusting for population structure and test performance. Infection fatality ratios (IFRs) were calculated by comparing study estimates with reported cases and deaths. Results: Among 1, 164 individuals, the adjusted seroprevalence was 34.7% (95% CI 31.8-37.6). Half of the enrolled households had at least one positive participant. Seropositivity increased in more densely populated areas (spearman's r=0.63; p=0.009). Individuals aged 20-59 years had at least two-fold higher seropositivity than those aged 0-9 years. The IFR was 40 per 100, 000 infections, with individuals ≥60 years old having higher IFRs. Conclusion: Over one-third of Nairobi residents had been exposed to SARS-CoV-2 by November 2020, indicating extensive transmission. However, the IFR was >10-fold lower than that reported in Europe and the USA, supporting the perceived lower morbidity and mortality in sub-Saharan Africa.